Bridging Entrepreneurship Education Inequality through Artificial Intelligence - Husein, Muhammad Ahmi; Araminta, Lavinia Disa Winona; Syahrir, Nur Hilal Andi (Universitas Muhammadiyah Surakarta, 2024)
Over the past decade, rapid technological advancements have transformed educational practices, particularly during the COVID-19 pandemic, which accelerated the shift to digital learning. While these developments have broadened access to education, their effectiveness in fields like entrepreneurship education, especially in developing countries such as Indonesia, remains under-explored. This study examines the perspectives of Indonesian students on the efficacy of online and offline learning methods in entrepreneurship education, aiming to identify the most effective technological tools for supporting educational equity across the nation. Utilising a mixed-methods approach, including quantitative surveys and qualitative interviews, the study reveals a significant preference for offline learning due to its interactive and hands-on nature. However, challenges such as limited topic selection and variability in teaching quality were noted. Conversely, online learning is valued for its flexibility and accessibility, particularly in remote areas, though technical issues like poor internet connectivity and reduced interactivity hinder it. This study highlights the potential of Artificial Intelligence (AI) to bridge these gaps by offering personalised interactive learning experiences that combine the benefits of both online and offline modalities. AI-driven platforms could address regional disparities in educational resources, providing all students with equal opportunities to develop entrepreneurial skills. The findings underscore the need for more tailored and dynamic educational approaches, suggesting that integrating AI into entrepreneurship education could enhance learning outcomes and promote greater educational equity across Indonesia. Future research should explore the implementation of AI in educational models to further understand its impact on student learning and regional development.